Designing Effective Privacy Notices and Controls - Schaub, Florian; Balebako, Rebecca; Cranor, Lorrie Faith (IEEE internet computing, 2017)
Privacy notice and choice are essential aspects of privacy and data protection regulation worldwide. Yet, today's privacy notices and controls are surprisingly ineffective at informing users or allowing them to express choice. We analyze why existing privacy notices fail to inform users and tend to leave them helpless, and discuss principles for designing more effective privacy notices and controls.